Circulation of Crimean-Congo Hemorrhagic Fever Virus in the former Yugoslav Republic of Macedonia revealed by screening of cattle sera using a novel enzyme-linked immunosorbent assay - Mertens, Marc; Vatansever, Zati; Mrenoshki, Slavcho; Krstevski, Kiril; Stefanovska, Jovana; Djadjovski, Igor; Cvetkovikj, Iskra; Farkas, Robert; Schuster, Isolde; Donnet, Fabien; Comtet, Loic; Tordo, Noël; et al. (Public Library of Science (PLoS), 2015)
There are only few assays available for the detection of Crimean-Congo Hemorrhagic Fever Virus (CCHFV)-specific antibodies in animals, and data about diagnostic sensitivity and specificity are incompletely documented for most of these tests. This is unfortunate since CCHFV antibodies in animals can be used as indicator for virus circulation in a geographic area and therewith potential risk of human exposure. This paper therefore reports on a novel ELISA for the detection of CCHFV-specific antibodies in cattle and on its application for testing ruminant sera from the Former Yugoslav Republic of Macedonia.